Malawi : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This first annual review of the Malawi Poverty Reduction Strategy (MPRS) assesses progress toward the implementation of pro-poor activities with a focus on inputs and annual outputs. The review assessed that the allocation of resources in the MPRS is more comprehensive than in the budget. It analyzes the central policy, which is implemented through the government budget and also reviews the macroeconomic and expenditure frameworks for the MPRS, targets, and implementation of pro-poor activities and recommendations.